Male mice are susceptible to brain dysfunction induced by early-life acephate exposure - Sasaki, Takahiro; Islam, Jahidul; Hara, Kenshiro; Nochi, Tomonori; Tanemura, Kentaro (Frontiers in Neuroscience, 2024)
Background: Acephate is a widely used organophosphate insecticide. Exposure to endocrinedisrupting chemicals, such as acephate, can interfere with neurodevelopment in childhood, increasing the risk of higher brain dysfunction later in life. Furthermore, brain dysfunction may be related to chemical exposure-related disturbances in the gut microbiota. However, the effects of early acephate exposure on the brains of adult males and females as well as on the adult gut environment remain poorly understood. Methods: This study investigated the effects of perinatal acephate exposure on the central nervous system and gut microbiota of mice, including sex differences and environmentally relevant concentrations. C57BL/6N pups were exposed to acephate (0, 0.3, 10, and 300 ppm) via the dam in their drinking water from embryonic day (E) 11.5 to postnatal day 14. We examined its effects on the central nervous system of adult males and females. Results: In the male treatment group, impairments in learning and memory were detected. Immunohistochemical analysis revealed a decrease in SOX2-, NeuN-, DCX-, and GFAP-positive cells in the hippocampal dentate gyrus in males compared to the control group, whereas GFAP-positive cells were fewer in females. In addition, gut microbiota diversity was reduced in both sexes in the experimental group.Our study demonstrates that the effects of early-life exposure to acephate are more pronounced in males than in females and can lead to a lasting impact on adult behavior, even at low doses, and that the gut microbiota may reflect the brain environment.